Users Experience Perspective In Exploring An Ancient Manuscript Using Augmented Reality Application - Nurul Fathihin Mohd Noor Shah; Riswadi Azmi; Masitah Ghazali; Nur Zuraifah Syazrah Othman (ICIC International, 2024)
Indexed by Scopus/ERA